Peran Pendidikan Islam dalam Membangun Kesetaraan Gender di Lingkungan Sekolah - Kalsum, Umi; Ningtias, Azzura Arum; Tambunan, Muhammad Bukhari; Sari, Herlini Puspita (Jurnal Pendidikan Agama Islam, 2025)
Abstract The issue of gender inequality remains a global challenge, including in the Muslim community. Although Islamic teachings uphold justice and equality as reflected in the Quran, the interpretation of gender bias in Islamic history has led to discriminatory practices against women. This study aims to analyze the role of Islamic education in building gender equality in the school environment, by highlighting Islamic principles that support gender justice and efforts to reinterpret religious texts that are more egalitarian. The research method used is a literature study by analyzing literature related to Islamic teachings on women, the history of Islamic thought on women's rights, and the role of education in shaping understanding of gender. The results of the study indicate that Islamic education has great potential in instilling the values ​​of gender equality in students through the delivery of comprehensive and fair Islamic teachings, as well as an introduction to the thoughts of progressive Muslim figures who defend women's rights. Reinterpretation of religious texts with a contextual approach and maqashid sharia is the key to eliminating gender bias and restoring the spirit of Islamic justice. Islamic education with a gender perspective can empower students to understand and practice the values ​​of equality in everyday life. Keywords : Gender equality, Islamic education, reinterpretation, gender bias, justice.